Surgical treatment outcome in Malignant glaucoma: Hospital-based single-center retrospective study (Central Asian Journal of Medical Sciences, 2025)
Objective: To determine the results of surgical treatment for malignant glaucoma among inpatients at the Department of Ophthalmology of the First Central Hospital and to evaluate the post-operative visual acuity, intraocular pressure, and the usage of intraocular antiglaucoma drops. Methods: A hospital-based, single-center, retrospective study of 19 patients treated for malignant glaucoma during the period from January 2019 to April 2023 at FCHM was conducted. Demographic and clinical data of cases were collected from medical records. Results: The average age was 74.5 ± 9.8 years. Female gender predominated, with 14 (82.3%) females and 16 (88.8%) eyes being pseudophakic. Of these, Pars plana vitrectomy (PPV) was performed in 9 (52.9%) cases, and transpupillary anterior vitrectomy (AV) was performed in 8 (47.1%) cases. Surgical capsulotomy and iridozonulatomy were done in all cases. The mean follow-up period was 11.44 ± 13.4 months (range, 2-38 months). The mean intraocular pressure decreased significantly from 39.4 ± 10.3 mmHg to 11.2 ± 3.2mmHg (p value < 0.01), and the number of antiglaucoma drops decreased significantly (p value < 0.01). In the anterior vitrectomy group, IOL removal surgery was performed in 2 cases due to recurrence detection. Conclusion: Pars plana vitrectomy surgery has been shown to improve visual acuity and effectively reduce intraocular pressure in patients with malignant glaucoma that is ineffective in laser and medical therapy. Transpupillary anterior vitrectomy, capsulotomy, and iridozonulectomy surgery are effective methods for reducing intraocular pressure and decreasing the need for antiglaucoma drops.